Nonlinear Electron Distribution Function in a Plasma - B´enisti†, D.; Friou, A.; Gremillet, and L. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we revisit the distribution function derived by making use of the adiabatic approximation, for electrons acted upon by a slowly varying electrostatic wave. This allows us to resolve an apparent paradoxical discrepancy between the results of two published papers, namely, V.B. Krapchev and A.K. Ram (1980), Phys. Rev. A 22, 1229-12242, and, D. B´enisti and L. Gremillet (2007), Phys. Plasmas, 14, 042304. We then briefly recall the relevance of the adiabatic approximation as well as its limitations, and further indicate how to go beyond this approximation to derive very accurate electron distribution functions.